Nutritional composition and health benefits of peas—a bibliometric research - Akin, Melekşen; Eyduran, Sadiye Peral; Mileševic, Jelena; Pavlovic, Suzana; Orahovac, Amil; Vasconcelos, Marta W.; Knez, Marija (Frontiers in Nutrition, 2025)
Pea (Pisum sativum L.) is a nutritious legume with health benefits, gaining attention as a functional food. Bibliometric studies use quantitative methods to assess research trends, gaps, and future directions. The main objective of this study was to provide a comprehensive overview of the fragmented literature on the nutritional profiles and health benefits of peas using a bibliometric approach. The analysis examined publications from 2013 to 2023, revealing trends in publication volume, author productivity, and international collaboration. Publications peaked in 2015, focusing on topics such as dietary fibers, carotenoids, phenolic compounds, and antinutrients affecting mineral bioavailability. Over the decade, the annual growth rate was 3.25%. The University of Saskatchewan produced the most influential research, with Warkentin TD as the most productive author. Canada and Poland had the highest number of publications, with the USA, China, and India following. Six major international co-authorship networks were identified, highlighting significant collaborations between countries. Key research themes included antioxidants, protein, fiber, and phytate in peas. This study provides a strong foundation for future integrated research, helping to better understand the potential of peas as a functional food and guiding more targeted studies to address current knowledge gaps across various disciplines.